Features of information systems audit in the digital economy - Wang, Wei; Havrys, Olha O. (Національний технічний університет "Харківський політехнічний інститут", 2024)
In the context of the digital economy, information systems audit professionals must not only master basic theoretical knowledge of auditing, but also acquire professional knowledge of information technology, become interdisciplinary professionals who can skillfully use information technology to collect and analyze data, and have the ability and experience to evaluate data for information system management.
Keywords: Information systems audit; digital economy; information systems